Amnesty in El Salvador: The Long and Winding Road to Justice, Truth, and Memory - Hatcher, Rachel (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
Using the lens of memory and the figure of the memory entrepreneur, this article traces the struggle between Salvadoran actors who support amnesty and forgetting and so do not wish investigations into the human rights violations committed during the war to take place, and actors who oppose amnesty and promote memory, truth, and justice. I argue that, as this latter group (i.e., human rights memory entrepreneurs) chipped away at the 1993 unconditional Amnesty Law in Salvadoran courts and in the Inter-American Human Rights System (IAHRS), creating a possibility for memory, state memory entrepreneurs worked to eliminate these possibilities.